Correlation of density and properties of particleboard from coffee waste with urea-formaldehyde and polymeric methylene diphenyl diisocyanates - Pornchai Rachtanapun (2018)
The effect of urea-formaldehyde adhesive and polymeric methylene diphenyl diisocyanates adhesive on the manufacture of particleboard using coffee waste as a raw material was investigated. The coffee waste was blended with the urea-formaldehyde or polymeric methylene diphenyl diisocyanates, then hot-pressed at 140°C at two pressure levels. The particleboards were tested to certify their density, moisture content, thickness swelling, water absorption, bending strength and modulus of elasticity. The density, moisture content and bending strength of the sample increased, but thickness swelling and water absorption decreased with increasing quantity of the urea-formaldehyde and polymeric methylene diphenyl diisocyanates. The particleboard with urea-formaldehyde and polymeric methylene diphenyl diisocyanates at the same quantity, the density, moisture content, thickness swelling, water absorption, bending strength and modulus of elasticity of polymeric methylene diphenyl diisocyanates were better than urea-formaldehyde adhesive. At the same adhesive content, the urea-formaldehyde adhesive samples above 18% urea-formaldehyde content and all of the samples with PMDI adhesive met the Thai industrial standards. © The Author(s) 2012 Reprints and permissions: http://www.sagepub.co.uk/journalsPermissions.nav.